A Factors Relating to The Behavior of Latrine Use in Klapasawit village, Purbalingga - Deti Sri Maharani, Alifka; Nurfadlilah Suhardi, Syifa; Sarwani Sri Rejeki, Dwi; Pramatama Mars Wijayanti, Siwi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Sanitation is crucial for environmental health as it helps reduce disease transmission and related health issues. In Indonesia, sanitation problems persist, often tied to socio-cultural factors, such as the habit of open defecation. In 2021, 83.28% of households in Central Java Province had adequate sanitation, while in Purbalingga Regency, it was 76.33%. Klapasawit Village, within the Kalimanah Health Centre's area, has yet to achieve open defecation-free status. This study analyzes the factors influencing latrine use behavior in Klapasawit Village, Kalimanah District, Purbalingga Regency. This quantitative analytical research used a cross-sectional design. The population was the entire Klapasawit village, and the sample met specific criteria. Proportionate stratified random sampling was employed, resulting in 90 samples. Instruments included questionnaires, interviews, camera recorders, and secondary data forms. Univariate analysis revealed that the age group of 36–45 years (41.1%) dominated the community, with women making up the majority (45.6%). Most had a primary school education (33.3%) and were housewives (32.2%). Bivariate analysis showed no significant correlation between knowledge, attitudes, infrastructure, family support, and the role of health workers in latrine use in Klapasawit Village, Kalimanah District, Purbalingga Regency.